PENGUNGKAPAN SUKARELA OLEH PERUSAHAAN KELUARGA DI INDONESIA: SEBELUM DAN SETELAH PENGADOPSIAN IFRS - Enung Nurhayati; Siti Nuke Nurfatimah (Jurnal Riset Keuangan dan Akuntansi, 2020)
This research is a research development of Darmadi Sodikin (2013). This study confirms differences in voluntary disclosure by family ownership before the adoption of IFRS (in 2008) and after the adoption of IFRS (in 2013). This study also provides additional analysis to determine the effect of IFRS adoption and voluntary disclosure on family companies in Indonesia. This study uses 23 samples of family companies in Indonesia. The dependent variable (voluntary disclosure) is accepted by the 49 disclosure index checklist method (Komsiah, 2005; Darmadi Sodikin, 2013). The independent variable (adoption of IFRS) is supported by dummy variables. This study provides evidence of the average voluntary disclosure presented by family companies after the adoption of IFRS more than before the adoption of IFRS. Disclosure items are presented more than disclosing more family company information. In addition, this study also proves that the adoption of IFRS has a positive impact on voluntary disclosures presented by family companies. Keywords: Voluntary Disclosure, Family Companies, Adoption of IFRS